Abstract

No abstract available.

Full Article  |  PDF Article

References

  • View by:
  • |
  • |

  1. Phil. Mag., Sept.1913, p. 423.

1913 (1)

Phil. Mag., Sept.1913, p. 423.

Phil. Mag. (1)

Phil. Mag., Sept.1913, p. 423.

Cited By

OSA participates in Crossref's Cited-By Linking service. Citing articles from OSA journals and other participating publishers are listed here.

Alert me when this article is cited.


Figures (2)

Fig. 1
Fig. 1

(Photographic and Visual Reaction)

Equations (21)

Equations on this page are rendered with MathJax. Learn more.

I = I 0 e - kz .
( dE ) V = I 0 ( 1 - e - hVz ) dt ,
( dE ) v = I 0 ( 1 - e - hvz ) dt .
edv = I 0 ( e - hvz - e - hVz ) dt .
e - hvz Q ,             e - hV 2 Q 0 and I 0 dt e dE .
dQ Q ( Q - Q 0 ) = - hzdE
1 Q = 1 Q 0 - ( 1 Q 0 - 1 ) e - hzEZ 0
v = 1 hz log [ 1 Q 0 - ( 1 Q 0 - 1 ) e - hzEQ 0 ] .
D = A log ( B - ( B - 1 ) e - hzE / B ,
( EC - 1 ) ( 1 - ( B - 1 ) e - cE ) = B - 1
dE = ( I 0 n - I t n ) 1 n ( 1 - e - hvz ) dt .
E ( I 0 n - I t n ) 1 n t e .
edv - m ( V - v ) dt = I 0 ( e - hvz - e - hVz ) dt ,
mv - I 0 e - hvz = m V - I 0 e - hVz = constant C ,
v = C m + I 0 hz
e dv dt = m V - ( m + I 0 kz ) v . = a - bv , say .
log a - bv a - bv 0 = bt , or v - v 0 = ( 1 - e - bt ) × constant ,
δ I 0 I 0 = P = P m + ( 1 - P m ) I 0 n I t - n
d v d ( log I 0 ) = 1 P m + ( 1 - P m ) I 0 - n I t n
v = 1 n P m log [ I + P m ( I 0 n I t - n - 1 ) ]
e - P m V ( 1 + P m ( I 0 n I t - n - 1 ) ) 1 n = constant